Prevalence and cost estimation for identification of positive tuberculosis among household contacts in Mandalay City, Myanmar - Kyaw Ko Ko Htel (Prince of Songkla University, 2018)
Thesis (M.Sc. (Epidemiology (International program)) Prince of Songkla University, 2016